KAJIAN PROSES PRODUKSI DAN TINGKAT KESUKAAN KONSNMEN TERHADAP MI SAGU TRADISIONAL RIAU - Yeni Kusumawaty; Shanti Fitriani (Universitas Riau, 2011)
The potential of sago in Indonesia is ver>- substantial, and Riau Province Is potential area which hasutilized sago as its main commodity. This research was conducted in Kepulauan Meranti District and PekanbaruCity in order to: 1) study the process of making traditional sago noodle, 2) identify consumer preferences. Themctliod used in this study wassurvcj' on sago noodle producers and consumers in Kepulauan Meranti Districtand consumers in Pekanbaru city. Primary data collection was done by structured interview to the producersand consumers, w hereas secondary data was obtained from related institutions. Descriptive a nalysis wascarried out to describe outline of sago noodle production process and level of consumer preferences for sagonoodle (prel'ercnce test with liedonic scales I -5) were analjized by independent sample t-test. The conclusionsof this study are: I) Traditional noodle making process consists of two methods, by boiling (grayish sagonoodle) and steaming (transparent white sago noodle), 2) According to t-test, the level of consumer preferencesof Pekanbaru City and Kepidauan Meranti Dtstriet were not significantly different for color and aroma ofwhite and gray sago noodle, but significantly different for the texture of sago noodle where the softer textureof the gray one is preferred.